Electroforming : a unique metal fabrication process - Parkinson, Ron (Technical series (Nickel Development Institute (Canada)), 1998)
This publication provides the basic principles of the process and the reasons why nickel is so dominant is briefly explained. Applications are described to demonstrate the versatility of electroforming in order that new applications may become apparent to those not already familiar with the process.